Emerging causes of anticancer therapies−induced Stevens-Johnson syndrome and toxic epidermal necrolysis: evidence from disproportionality analysis of the FDA adverse event reporting system - Liu, Wensheng; Song, Xue; Du, Qiong; Liu, Jiyong (Frontiers in Immunology, 2025)
BackgroundStevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are potentially fatal cutaneous adverse events of drug treatment. Evidence for SJS/TEN risk from current anticancer therapies in population-based studies is scarce.ObjectiveThe present study aims to characterize the profiles and risk factors of SJS/TEN related to contemporary anticancer regimens.MethodsReported odds ratios (ROR) were employed to identify anticancer drugs associated with SJS/TEN development using FAERS data from January 2004 to September 2024. Single factor, LASSO, and multivariable logistic regression analysis were performed to explore the risk factors of SJS/TEN related to anticancer therapies. Weibull shape parameter analysis was applied to the onset time of reported SJS/TEN.ResultsA total of 3471 unique SJS/TEN events were identified for 159 anticancer drug pairs, of which 31 drugs were identified as significantly disproportionate. Targeted therapies accounted for 35.93% of pairs, chemotherapies for 35.52%, and immunotherapies for 21.52%. The median onset time of SJS/TEN with anticancer therapies was 17 days. Moreover, multivariable logistic regression showed that age exceeding 65, female gender, and 10 anticancer drugs were significant risk factors for anticancer therapy-related SJS/TEN.ConclusionsThis study provides real-world evidence regarding the burden of SJS/TEN associated with anticancer therapies. Addressing this knowledge gap will facilitate the optimization of clinical management for SJS/TEN. Further research to establish causality and inform clinical decision-making related to anticancer therapy-associated SJS/TEN is urgently needed.